Experiences of youth with medical complexity and their families during the transition to adulthood: a meta-ethnography - Li Lin; Bird Marissa; Carter Nancy; Ploeg Jenny; Gorter Jan Willem; Strachan Patricia H. (De Gruyter, 2020)
Youth with medical complexity (YMC) are a small subset of youth who have a combination of severe functional limitations and extensive health service use. As these youth become adults, they are required to transition to adult health, education, and social services. The transition to adult services is especially difficult for YMC due to the sheer number of services that they access. Service disruptions can have profound impacts on YMC and their families, potentially leading to an unsuccessful transition to adulthood. This meta-ethnography aims to synthesize qualitative literature exploring how YMC and their families experience the transition to adulthood and transfer to adult services. An in-depth understanding of youth and family experiences can inform interventions and policies to optimize supports and services to address the needs of this population at risk for unsuccessful transition to adulthood. Using Noblit and Hare's approach to meta-ethnography, a comprehensive search of Medline, CINAHL, Embase, PsycINFO, Social Sciences Index, and Sociological Abstracts databases, supplemented by hand searching, was conducted to identify relevant studies. Included studies focused on the transition to adulthood or transfer to adult services for YMC, contained a qualitative research component, and had direct quotes from youth or family participants. Studies were critically appraised, and data were analyzed using meta-ethnographic methods of reciprocal translation and line of argument synthesis. Conceptual data from ten studies were synthesized into six overarching constructs: (1) the nature and process of transition, (2) changing relationships, (3) goals and expectations, (4) actions related to transition, (5) making sense of transition, and (6) contextual factors impacting transition. A conceptual model was developed that explains that youth and families experience dynamic interactions between their goals, actions, and relationships, which are bounded and influenced by the nature, process, and context of transition. Despite the tremendous barriers faced during transition, YMC and their families often demonstrate incredible resilience, perseverance, and resourcefulness in the pursuit of their goals. Implications for how the conceptual model can inform practice, policy, and research are shared. These implications include the need to address emotional needs of youth and families, support families in realizing their visions for the future, promote collaboration among stakeholders, and develop policies to incentivize and support providers in implementing current transition guidelines.